2013
DOI: 10.1038/ncomms2932
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous nickel hydroxide nanospheres with ultrahigh capacitance and energy density as electrochemical pseudocapacitor materials

Abstract: Among numerous active electrode materials, nickel hydroxide is a promising electrode in electrochemical capacitors. Nickel hydroxide research has thus far focused on the crystalline rather than the amorphous phase, despite the impressive electrochemical properties of the latter, which includes an improved electrochemical efficiency due to disorder. Here we demonstrate high-performance electrochemical supercapacitors prepared from amorphous nickel hydroxide nanospheres synthesized via simple, green electrochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
415
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,099 publications
(450 citation statements)
references
References 31 publications
25
415
3
Order By: Relevance
“…On the other hand, recent research implies that amorphous structure is commensurate with crystalline materials in supercapacitors owing to the similar reason. 22 Figures 5c and d are the high resolution X-ray photoelectron spectroscopy spectra of Ni 2p and Co 2p for NiCo 2 O 4 annealed at 300°C, respectively. It shows that the surface of the sample has a composition containing Ni 2+ , Ni 3+ , Co 2+ and Co 3+ with two and one shakeup satellites, respectively.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…On the other hand, recent research implies that amorphous structure is commensurate with crystalline materials in supercapacitors owing to the similar reason. 22 Figures 5c and d are the high resolution X-ray photoelectron spectroscopy spectra of Ni 2p and Co 2p for NiCo 2 O 4 annealed at 300°C, respectively. It shows that the surface of the sample has a composition containing Ni 2+ , Ni 3+ , Co 2+ and Co 3+ with two and one shakeup satellites, respectively.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…The reaction process was facile and efficient, simply involving heating the reactants under reflux in ethylene glycol for 1 h. Yang and colleagues [76][77][78] have also contributed to the synthesis of amorphous hydroxide materials by preparing flower-like spherical nanostructures using a unique electrochemical technique that is simple, green and inexpensive. These spheres and hollow structures are interesting candidates for use in energy storage [94].…”
Section: Science China Materialsmentioning
confidence: 99%
“…The large number of under-coordinated atoms (good electron acceptors) and reactive sites at the surface means that amorphous materials also have the advantage over crystalline ones in their contact with the electrolyte and active substances (electron donors), which favors electrochemical processes. In regard to the merits discussed above, amorphous nanomaterials have already demonstrated their superior performance over bulk crystalline materials in various electrochemical applications, including lithium-and/or sodium-ion batteries [51,62,66,71,79,84,[96][97][98][99][100], super-or pseudo-capacitors [77,78,83], electrochemical water splitting [59] and sensors [72,81]. The amorphous CoSnO 3 @C nanoboxes reported by Wang et al [79] showed high initial discharge and charge capacities of around 1,410 and 480 mA h g −1 , respectively, as revealed in Fig.…”
Section: Applications Electrochemical Electrode Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, amorphous electrode material was preferred over the crystalline material owing to the fact that amorphous materials demonstrated moderate structural disorder facilitating faster ion diffusion by forming irregular surfaces providing high specific surface area and suitable pore size distribution 187, 188. The fabricated all‐solid state device exhibited a large specific capacitance of 350.2 F g −1 at 0.5 A g −1 current density while maintaining a good rate capability of 159.5 F g −1 even at high current density of 20 A g −1 .…”
Section: Fiber‐shaped Energy Storage Devicesmentioning
confidence: 99%